The Effect of Covid-19 on Increasing E-Commerce Sales in Various Fields - Taufik Hidayat; Yasep Azzery (Sultan Publisher, 2022)
The Covid-19 pandemic forced the government to implement activity restriction obligations starting in March 2020. Even though Covid-19 paralysed physical activity, on the other hand, this has also made online sales increase sharply. According to the report